Performance comparison between plastic-based fiber bundle and multimode fused coupler as probes in displacement sensors - Yasin, M.; Harun, Sulaiman Wadi; Pujiyanto, A.; Ghani, Z.A.; Ahmad, Harith (IOP Publishing, 2010)
Fiber optic displacement sensors with bundled and fused coupler fiber probes are being investigated. The effects of axial displacements on the detected output voltages are also investigated for fiber bundle probe sensor. The resolutions obtained are 0.9 and 4.0 mu m, for the front and back slopes, respectively. A comparison is made with a commercial plastic based multimode fused coupler which gives a better range of 2.0 mm. This is longer than that achieved by the fiber bundle probe which is only 0.4 mm and has a lower resolution of 34 mu m for the case of 50:50 coupling ratio.